Pengelolaan Zakat, Infaq Dan Sedekah Di Kota Medan Analisis Kinerja Masjid-Masjid, ACT Dan BAZNAS Tahun 2015-2019 - I Ibrahim (Jurnal Penelitian Medan Agama, 2020)
Law No. 23 of 2011 provides institutional strengthening in integrated zakat management into an integrated system. The research aims to answer the problem How to manage ZIS, What are the implications of Law No. 23 on the collection and distribution of ZIS and Are there any obstacles encountered in the management of Zakat. This research is a qualitative study using the approach of legal sociology. The results showed; (1) that the Implementation of Management Law No. 23 of 2011 in the management of ZIS management has not been implemented optimally in accordance with the mandate of Law No.23 of 2011; (2) the impact of the implementation of Law No.23 of 2011 has not been maximized, as evidenced by the minimal amount of zakat receipts and its management and allocation are unclear; (3) The constraints in managing ZIS are very influential on the interest to pay ZIS in mosque, ACT and BAZNAS Medan City.